Human Capital Quality and Aggregate Income Differences: Development Accounting for U.S. States - Eric A. Hanushek; Jens Ruhose; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2015)
Although many U.S. state policies presume that human capital is important for state economic development, there is little research linking better education to state incomes. In a complement to international studies of income differences, we investigate the extent to which quality-adjusted measures of human capital can explain within-country income differences. We develop detailed measures of state human capital based on school attainment from census micro data and on cognitive skills from state- and country-of-origin achievement tests. Partitioning current state workforces into state locals, interstate migrants, and immigrants, we adjust achievement scores for selective migration. We use the new human capital measures in development accounting analyses calibrated with standard production parameters. We find that differences in human capital account for 20-35 percent of the current variation in per-capita GDP among states, with roughly even contributions by school attainment and cognitive skills. Similar results emerge from growth accounting analyses.
Keywords: I25; O47; J24; 330; economic growth; human capital; cognitive skills; schooling; U.S. states